2021
DOI: 10.21203/rs.3.rs-208808/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sustained Delivery of MMP-9 siRNA via Thermosensitive Hydrogel Accelerates Diabetic Wound Healing

Abstract: Excessive expression of matrix metalloproteinase 9 (MMP-9) impedes healing of diabetic chronic wounds, thus wound dressing that could effectively inhibit the expression of MMP-9 offers significant clinical translation for diabetic wound healing. Herein, a hybrid hydrogel dressing was developed for localized and sustained delivery of MMP-9 siRNA (siMMP-9). siMMP-9 was complexed with Gly-TETA (GT), the GT/siMMP9 complex was then loaded into a thermosensitive hydrogel based on Pluronic F-127 (PF) and methylcellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Stalling et al [ 67 ] confirmed that cultured human dermal fibroblasts in the presence of methyl cellulose hydrogels in vitro did not result in significant changes in cell viability after 5 days, indicating the non-cytotoxic of this material. Lan et al [ 68 ] developed hydrogel dressing made of Pluronic F-127 and methyl cellulose for localized and sustained release of siMMP-9 to treat diabetic chronic wounds. Excessive expression of matrix metalloproteinase 9 (MMP-9) impaired the healing of chronic diabetic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Stalling et al [ 67 ] confirmed that cultured human dermal fibroblasts in the presence of methyl cellulose hydrogels in vitro did not result in significant changes in cell viability after 5 days, indicating the non-cytotoxic of this material. Lan et al [ 68 ] developed hydrogel dressing made of Pluronic F-127 and methyl cellulose for localized and sustained release of siMMP-9 to treat diabetic chronic wounds. Excessive expression of matrix metalloproteinase 9 (MMP-9) impaired the healing of chronic diabetic wounds.…”
Section: Discussionmentioning
confidence: 99%